Towards Science with LSST: Data Products and Communications: Workshop 7. Issue Volume 14:Issue S339(2018) (November 2017) - Graham, M. L.
Abstract: The main purpose for holding a Workshop about the Large Synoptic Survey Telescope (LSST) was to move all participants further towards answering the question, "How will I do my science with LSST data?" Presentations included (i) the planned pipelines and products of the data management team, and (ii) the existing channels for communication within the science community and between the community and the LSST Data Management team. In between the formal presentations, small groups discussed matters such as how to select the data products or communications resources that were best suited to individual science goals. The latter discussions were designed both to facilitate engagement with the material and to foster collaboration. Participants should thus have become better equipped to continue on their respective individual paths towards science with LSST.